Effects of opioid-sparing general anesthesia on postoperative nausea and vomiting in laparoscopic gynecological surgery - Sun Woo Nam; Sang-Hwan Do; Jung-Won Hwang; Insun Park; Insung Hwang; Hyo-Seok Na (Korean Journal of Anesthesiology)
Background In this study, we aimed to investigate whether opioid-sparing anesthesia (OSA) reduces postoperative nausea and vomiting (PONV) in patients undergoing laparoscopic gynecological surgery. Methods Adult patients undergoing elective laparoscopic gynecological surgery were randomly assigned to either the opioid-using anesthesia (OUA) or the OSA groups. In the OUA group, remifentanil was administered as an opioid during general anesthesia. In the OSA group, apart from a single dose of 5 μg/kg of alfentanil for tracheal intubation, no other opioids were used. In both groups, a multimodal intravenous non-opioid analgesic regimen was used preferentially in the post-anesthesia care unit (PACU). The primary outcome was the incidence of PONV, assessed by symptoms until the postoperative day 1. Results A total of 120 patients were included in this study. The incidence of nausea in the PACU was significantly lower in the OSA group compared to in the OUA group (31.7% in the OSA group vs. 51.7% in the OUA group, P = 0.026). Pain scores and the incidence of opioid analgesic administration were lower in the OSA group during PACU stay, resulting in a significantly lower number of patients requiring rescue opioid analgesics (3.3% vs. 18.3%, P = 0.008). There were no significant differences in intraoperative vital signs, hemodynamic interventions, or duration of PACU and hospital stay between the two groups. Conclusions OSA significantly reduced postoperative nausea, pain scores, and the need for rescue analgesics in the PACU without increasing hemodynamic instability in patients undergoing laparoscopic gynecological surgery.